Analysis of the Influence of Traditional Market and Modern Market Image on Consumer Loyalty (Case Study at Pd Ya'ahowu, Gunungsitoli City) - Heniwati Gulo; Dedi Irawan Zebua (Economic Education Analysis Journal, 2025)
This study aims to This study aims to analyze: (1) the influence of traditional market image on consumers; (2) the impact of conventional market image on consumer loyalty; (3) the influence of consumer satisfaction on consumer loyalty; and (4) the influence of traditional markets on consumer loyalty with consumer satisfaction as a mediating variable at PD Ya'ahowu Gunungsitoli City. Using a quantitative approach with multiple linear regression analysis methods. The sample of this study involved 77 respondents selected using a purposive sampling technique. Taken by accidental sampling. The data collection technique used a questionnaire through validity and reliability tests. The requirements for the regression test used the classical assumption test. The results of this study prove that the image of traditional and modern markets significantly affects consumer loyalty at PD Ya'ahowu Gunungsitoli City. The implications of this study confirm that PD Ya'ahowu Gunungsitoli City needs to improve the brand image of traditional markets by designing more effective strategies to increase productivity, build a comfortable shopping environment, and provide good service and product quality.